Comparison of hepatitis C treatment outcomes between telehepatology and specialty care clinics in the era of direct-acting antivirals. (September 2021) - Case, Lindsay; Wright, Jason; Ryan, Yvette
Introduction: Telehealth technologies for rural patients are increasingly being used to deliver care within the Department of Veterans Affairs (VA), and treatment of hepatitis C virus (HCV) is no exception. However, data evaluating outcomes with telehealth compared with specialty clinics in the era of direct-acting antiviral (DAA) agents is sparse. Methods: In a retrospective analysis, we compared treatment outcomes for patients receiving DAAs followed solely in a telehepatology clinic (telehealth) versus an in-person specialty care clinic (standard of care) at the VA Eastern Colorado Health Care System. Patients with decompensated cirrhosis (CTP-B or CTP-C) were excluded from the study as they were exclusively followed via standard of care. Provider overlap occurred between clinics and consisted of physician specialists (hepatology and infectious diseases), physician assistants and clinical pharmacists. Results: From 1 January 2014 to 31 December 2017, we treated 764 veterans for HCV infection. Standard of care was provided to 629 patients representing 654 treatment courses, and telehealth was provided to 135 patients representing 138 treatment courses. Sustained virologic response rates were not significantly different between the two clinics when looking at total treatment courses (93% telehepatology vs 89% specialty care, p = 0.203) and individual patients treated (95% telehepatology vs 93% specialty care, p = 0.377). Discussion: Hepatitis C treatment utilizing telehealth technologies to improve access to care does not negatively impact treatment outcomes when compared with specialty care clinics in the era of DAAs.